PERBEDAAN PENILAIAN CITA RASA DAN SISA HIDANGAN SAYURBERDASARKAN PENGEMBANGAN RESEP PADA PASIEN KELAS III DENGAN DIET BIASA DI RUMAH SAKIT UMUM DAERAH KOTA SEMARANG - Dini Febianti; Ana Yuliah Rahmawati; Heni Hendriyani; Dyah Nur Subandriani (JURNAL RISET GIZI, 2015)
Background : the remaining vegetable dishes at the hospital are still high, this is evident from the results of interviews with Semarang City Hospital nutritionists, it is known that the average remaining vegetable is 35%.Objective : to determine the differences in the assessment of taste and leftover vegetable dishes based on the development of recipes in class III patients in Semarang City Hospital.Methods : including institutional nutrition research with the type of pre-experimental research using the one group pretest-posttest design with 36 samples. Samples were all class III patients in Semarang City General Hospital who received regular food. Data collected includes assessing the taste and leftovers of patients. The test used is Wilcoxon with a probability 0.05.Results : A total of 97.2% of the samples expressed satisfaction over the size of portions, taste, presentation, color, and maturity of food development recipes; 94.4% of samples expressed satisfaction with the texture and aroma of food development recipes; 91.6% of the samples expressed satisfaction with the food seasoning for prescription development; 72% of the sample left little food on the plateau. There was no difference in taste of food before and after the development of the recipe, but there were differences in leftovers before and after the development of the recipe.Conclusion : the results of the recipe development have many leftovers rather than the initial recipe even though the results of the taste evaluation are equally satisfying. It is recommended to test the cuisine first before developing a recipe.